Comparison of Biochemical Parameters in the Treatment of Rickets (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The correct tactics for the treatment of rickets is an indispensable component of the correction of disorders of phosphorus-calcium metabolism in a growing child in modern conditions. 203 children under the age of 1 year were examined. In all children, the level of 25(OH)D in the blood serum, the level of calcium and phosphorus were determined. The proposed scheme of individual prescription of vitamin D preparations for children with rickets in combination with calcium preparations and general strengthening therapy made it possible to significantly increase the effectiveness of treatment. At the same time, there is a decrease in the clinical manifestations of rickets, its residual effects, symptoms of spasmophilia and an increase in the content of 25(OH)D3 in the blood serum.